The aesthetics of the eyes and mouth position in a three-point face schema - Frąckiewicz, Waldemar (Anthropological Review, 2001)
Oculographical research of people watching a human face indicates that beholder.s eyes stop most often and for the longest period of time on the eyes and the mouth of the face looked at and that they move among these three points most frequently. The position of the eyes and mouth in relation to one another can be described with a single number being a measure of an angle with the vertex in the middle of the mouth and with arms crossing the centers of the eye pupils. The angles were measured from photographs of people from all over the world, as well as of residents of Lublin. Subsequently, the subjects from Lublin were asked to make face schemas by positioning the eyes and the mouth in the way they considered most attractive. The eye-mouth-eye angle of these schemas was measured. Additionally, measurements of the same angle were taken from the faces depicted on icons. The schemas of the most attractive . according to the subjects . faces were characterized by angles approximating the mean angle from the photographs, and significantly greater than the mean angle from the icons.